Stabilization of inverted pendulum system using discrete sliding mode control - Ngadengon, Rafidah; Tomari, Razali Md; Hamdan, Rohaiza; Ngadengon, Zuraihah; Mat Akir, Rohaida
This paper presents the development of Discrete Sliding Mode Control (DSMC) to control an inverted pendulum systems. The mathematical model of inverted pendulum system is linearized using Taylor expansion method. The linear sliding surface was used to design the DSMC using equivalent method. The system is designed with additional matched external disturbance to validate the robustness of the controller. The findings demonstrated that the proposed controller’s capable to track the reference tracking and provide better response compared to Discrete Linear Quadratic Regulator (DLQR)